2014
DOI: 10.1017/jfm.2014.535
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of pulsatile flow through model abdominal aortic aneurysms

Abstract: To contribute to the understanding of flow phenomena in abdominal aortic aneurysms, numerical computations of pulsatile flows through aneurysm models and a stability analysis of these flows were carried out. The volume flow rate waveforms into the aneurysms were based on measurements of these waveforms, under rest and exercise conditions, of patients suffering abdominal aortic aneurysms. The Reynolds number and Womersley number, the dimensionless quantities that characterize the flow, were varied within the ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 37 publications
1
25
0
Order By: Relevance
“…Indeed, Gopalakrishnan et al (2014) have shown that small changes in the AAA geometry can significantly affect the WSS distribution, and changes in the curvature of the vessel wall have also been shown to affect WSS (Siggers & Waters 2008). In the current study we demonstrated results in two patient geometries, however, we also performed similar simulations in a total of six patient geometries and observed similar WSS LCS structures influencing the observed near wall concentration fields.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Gopalakrishnan et al (2014) have shown that small changes in the AAA geometry can significantly affect the WSS distribution, and changes in the curvature of the vessel wall have also been shown to affect WSS (Siggers & Waters 2008). In the current study we demonstrated results in two patient geometries, however, we also performed similar simulations in a total of six patient geometries and observed similar WSS LCS structures influencing the observed near wall concentration fields.…”
Section: Discussionmentioning
confidence: 99%
“…A similar conclusion was made by Le et al [17] and Cebral et al [19] based on their CFD simulations of cerebral aneurysms in rabbits and humans, respectively. In contrast, Gopalakrishnan et al [18] stated that, by increasing Re, the strength of the main vortex structure increases.…”
Section: Introductionmentioning
confidence: 94%
“…In contrast, Le et al [17] stated that Womersley number does not affect the flow feature and structures based on their CFD simulations of an IA from a rabbit. Furthermore, Gopalakrishnan et al [18] stated that while Womersley number does not change the vortex mode, but high Womersley number is associated with weak vortex rings in their simulation on abdominal aortic aneurysms. Bouillot et al [10] concluded that Re has a negligible effect on the flow structures of an idealized sidewall intracranial aneurysm for a steady inflow according to their PIV measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Aneurysms are pathologic dilations of the vessel wall, and their flow characteristics have been extensively investigated as mechanically and biologically related with the initiation, growth, and eventual rupture of aneurysms (Cebral et al 2011;Geers et al 2011;Schnell et al 2014;Gopalakrishnan et al 2014;Arzani et al 2016).…”
Section: Cerebral Arteries With Aneurysmsmentioning
confidence: 99%